(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Many studies were conducted on the subject in home and abroad but there is none in Chittagong, Bangladesh. To know about top three risk factors for coronary artery disease we conducted the study. Methods: It was a retrospective study. Records of a private cardiac center from July 2013 to June 2014 was collected. Only coronary stenosed cases (As per angiogram) was studied. Age, sex, BMI, diabetes mellitus, hypertension, smoking and other risk factors were considered. Collected data was managed manually. Finally discussion was made and conclusion was done. Results: Majority cases 58(76%) were of 40-60 years age group. Male preponderance was there 64(83%). BMI of 45(60%) cases was normal (<25). Family history was positive among 11(14%) cases. Dyslipidemia was found in 08(10%) cases, 56(73%) cases were hypertensive, 43(56%) cases were type-2 diabetic and 35(45%) were smoker. Conclusion: Hypertension, Diabetes and Smoking are top 03 risk factors for coronary artery disease. All are modifiable. So, primordial prevention should be taken to reduce prevalence of coronary artery disease. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 26-28